Visible Light Catalytic Degradation of Aniline Wastewater over Multishaped BiOBr Microcrystals - Jun Zhang; Huabo Li; Hairui Yao; Hao Zhang (Journal of Chemistry)
The photooxidation process of aniline-containing simulated wastewater under visible light irradiation over BiOBr microcrystal grains with different shapes was studied. The distinctive surface microstructures of the BiOBr microcrystals, like clustered flower petals and quadrate lamellas, were produced by using imidazole ionic liquid and inorganic bromide as Br sources and by solvothermal and hydrothermal route, respectively. The ionic liquid not only can impact the products’ morphology, but also can largely improve the photocatalytic activity of the BiOBr microcrystals due to the soft templating effect. The top degradation ratio of the aniline wastewater photocatalyzed by lamellar BiOBr crystals is 23.71%, but the equivalent value photocatalyzed by flower petal-like BiOBr crystals is almost twice as much; that is, it reaches 46.51%. The photodegradation effect and mechanism over differently shaped BiOBr microcrystals have been compared.